(untitled) (Journal of the College of Basic Education, 2022)
The objective of the research was to detect the effect of ballistic training on legs explosive power for elite soccer players, throw preparation of a curriculum in training ballistic exercises with soccer players, and the use of these exercises will develop explosive power through a vertical jump test, as well as the impact of these exercises to develop the skill of kicking the ball as far away as possible, the post test was conducted on the 20 soccer team players from University of Technology, then the sample was divided into two groups, control and experimental, in a pairing method and underwent the experimental group to training ballistic contains high and forward jump exercises, with weight addition for each player according to his optimum capacity to carry the weight on his shoulders when performing exercises. It appeared from the application of the experimental method and results of the study, that there was significant difference in vertical jump test and kicked the ball farther, for the experimental group, as a result, researcher concluded that using ballistic training was the reason for this significant difference favoring the experimental group and the development of explosive power came through the implementation of exercise training ballistic , which resulting in improved vertical jump and kicked the ball as far as possible. The researcher recommended further research in this area and with different groups age, and to see the impact of ballistic training on different samples to match players level and the quality of effectiveness to get the best results.